Observation of a Λ0b − ̄ Λ0b production asymmetry in proton-proton collisions at √s=7 and 8 TeV - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Journal of high energy physics, 2021)
Abstract: This article presents differential measurements of the asymmetry between Λ0b and Λ0b baryon production rates in proton-proton collisions at centre-of-mass energies of√s = 7 and 8 TeV collected with the LHCb experiment, corresponding to an integrated luminosity of 3 fb−1. The Λ0b baryons are reconstructed through the inclusive semileptonic decay Λ0b → Λ+c μ−νμX. The production asymmetry is measured both in intervals of rapidity in the range 2.15 < y < 4.10 and transverse momentum in 2 < pT < 27 GeV/c. The results are found to be incompatible with symmetric production with a significance of 5.8 standard deviations for both √s = 7 and 8 TeV data, assuming no CP violation in the decay. There is evidence for a trend as a function of rapidity with a significance of 4 standard deviations. Comparisons to predictions from hadronisation models in Pythia and heavy-quark recombination are provided. This result constitutes the first observation of a particle-antiparticle asymmetry in b-hadron production at LHC energies.
Im Titel ist "0" hoch- und "b" in Λ0b − ̄ Λ0b tiefgestellt, dabei steht jeweils "0" über "b"
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Im Titel steht das zweite lambda mit einem Oberstrich
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, G. Frau, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, N. Meinert, A.B. Morris, S. Neubert, M. Sarpis, M. Schmelling, D.J. Unverzagt, U. Uwer, H. Viemann, R. Waldi, C. Wang, L. Witola, M. Zavertyaev, A. Zhelezov, und weitere 955
Gesehen am 12.11.2021